Necrobiosis Lipoidica Diabeticorum - Andrea Scaramuzza; Maddalena Macedoni; Gian Luca Tadini; Laura De Angelis; Francesca Redaelli; Alessandra Gazzarri; Valentina Comaschi; Elisa Giani; Gian Vincenzo Zuccotti (Hindawi Limited, 2012)
Necrobiosis lipoidica is a rare disorder that usually appears in the lower extremities and it is often related to diabetes mellitus. There are few reported cases of necrobiosis lipoidica in children. We present an interesting case in that the patient developed lesions on the abdomen, which is an unusual location.